VALIDITY OF WORKSHEET ORIENTED STUDENT FACILITATOR AND EXPLAINING MODEL FOR STUDENTS IN THE TOPIC DYNAMICS OF ROTATION AND BALANCE OF RIGID BODIES (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2022)
The use of teaching materials in the learning process really helps the realization of an active, effective and efficient learning, as well as the discovery of concepts independently by students. One of the efforts to realize this as well as the aim of this research is to develop teaching materials in the form of physics learning worksheet oriented to the Student Facilitator and Explaining learning model which is valid for class XI students in the Science program at SMA Negeri 6 Padang. The type of research used is Research and Development (R&D). The research procedure was a 4-D model namely define, design, develop, and disseminate, but this stage was not carried out due to time constraints. The research instrument used was a validity questionnaire. Furthermore, the data obtained was analyzed to see the validity of the worksheet. The results showed that the Student Facilitator and Explaining oriented worksheet developed was categorized as valid with a percentage of 80.2%. The validity of the worksheet is illustrated by the results of validation by experts on the four aspects of the assessment, namely the appropriateness of the content, language and images, presentation, and graphics.Keyword : Worksheet, Student Facilitator and Explaining, Valid.